The Threat of Conventional Weapons to Nuclear Security: A New Reality for Deterrence - P. Rautenbach (Международная аналитика)
This paper explores the idea that developments in Conventional Prompt Global Strike (CPGS) systems degrade nuclear security. The United States is developing such weapons for niche conventional use on the surface, but the line between tactical and strategic weapons is becoming blurred. What is more, while there have been discussions in Congress surrounding the problem of missile ambiguity, there is a multitude of other problems, with the largest being that CPGS weapons inherently degrade nuclear security. By looking at the behavior of critical states and actors involved in the emergence of CPGS weapons and combining this with pre-existing literature and insight on similar topics within international relations, we then can conduct a thorough investigation on the impact of these CPGA systems. When compared to nuclear missiles, the increasing usability of these weapons is inherently dangerous, as it increases both the likelihood of their use and the likelihood of a first strike against another state’s nuclear deterrent. Traditionally, conducting a first strike has been all but impossible because it entailed using nuclear weapons, which come with ethical and environmental consequences. If nuclear weapons can be replaced or substituted with CPGS weapons, then a first strike becomes an actual possibility. Hence, as a result, the nuclear doctrine is changing to reflect this conventional danger and has led to a lower threshold for nuclear use. This fact then demonstrates clear signs that CPGS technology degrades nuclear security and thus increases the chance of nuclear use.